PEMAHAMAN KONSEP PERUBAHAN SIFAT BENDA PADA MATA PELAJARAN IPA MELALUI METODE EKSPERIMEN - Aprilia, Aprilia (Institut Agama Islam Negeri Palopo, 2018)
This study aims: to find out how to apply the experimental method in science subjects and to findout the improvement of students' understanding of the concept of changes in the nature of objectsusing the experimental method in fifth grade students of 164 Kaluku Elementary School,Sukamaju District, North Luwu District. This research is a classroom action research conductedin class V SDN 164 Kaluku District Sukamaju North Luwu district. Data collection techniques inthis study are tests, interviews, observations, and documentation. Data analysis was performedusing qualitative descriptive analysis. The results showed that: (1) With the application of theexperimental methods of class V students it was easier to understand material changes in thenature of objects in science learning; (2) By using the experimental method in the learningprocess which is carried out in stages, 2 cycles experience a significant increase where students'understanding of learning in cycle 1 is still categorized as